PEMANTAUAN DOSIS PERORANGAN MENGGUNAKAN THERMOLUMINESCENCE DOSIMETER (TLD) DI WILAYAH PAPUA DAN PAPUA BARAT TAHUN 2020-2021 - Fuadi, Nurul; Jusli, Nurlinda (SAINFIS: Jurnal Sains Fisika, 2022)
A study has been carried out with the title "Monitoring Individual Doses Using Thermoluminescence Dosimeters (TLD) in Papua and West Papua Regions 2020-2021. This study aims to determine the number of doses received by radiation workers in the Papua and West Papua regions so that they can anticipate the occurrence of excessive dose exposure and minimize the negative impact caused by radiation exposure. Radiation is the emission of energy in the form of waves or particles emitted by a radiation source or radioactive substance. Radiation worker is any person who works in diagnostic and interventional radiology installations who are expected to receive an annual radiation dose that exceeds the dose for the general public. Monitoring of individual doses received by radiation workers is mandatory. This is done to limit the radiation dose received by radiation workers as stated in PERKA BAPETEN no. 4 of 2013. After monitoring individual doses in Papua and West Papua, it can be concluded that no radiation worker received a dose exceeding the maximum dose limit determined by BAPETEN. The average effective dose is 20 mSv per year for a period of 5 (five) years, and 50 mSv in 1 (one) year.